A chromatography-free one-pot, two-step synthesis of 1,2,4-thiadiazoles from primary amides via thiolation and oxidative dimerization under solvent-free conditions: a greener approach - Rajput K.; Singh V.; Singh S.; Srivastava V. (My University, 2025)
An efficient and practical one-pot, two-step synthesis of 1,2,4-thiadiazoles from primary amides with Lawesson reagent (LR) and tert-butyl hydrogen peroxide (TBHP) without solvent is demonstrated for the first time. This groundbreaking and environmentally friendly approach utilises readily available starting materials and eliminates the use of traditional solvents in the reaction process. The broad substrate scope, excellent functional group tolerance in mild and metal-free conditions, quick conversion, and excellent yields are essential features of this methodology. All the compounds were purified without column chromatography. © 2024 The Royal Society of Chemistry.